Romance and chance in the city: two film adaptations of short stories by Julio Cortázar (Anclajes, 2024)
The masculine search for an idealized romantic love through urban journeys marked by chance is a recurring topic in the narrative of Julio Cortázar. We analyze and compare the film adaptations of two short stories by Cortázar, in which it is possible to recognize different modulations of this urban romance: Der gläserne Himmel (Germany, 1987), by Nina Grosse, based on the story “The Other Sky”; and Jogo subterraneo (Brazil, 2005), by Roberto Gervitz, based on “Manuscript Found in a Pocket”. Both films show the versatility of Cortazar's fictions to intersect with different genres, times and contexts. At the same time, they reconfigure the asymmetry in the construction of the male protagonists and the female characters, presented in Cortázar's narrative as symbols rather than as individuals.
Keywords: Argentine Literature; Film and Literature; Julio Cortázar; 20th century